2018
DOI: 10.1111/jvh.12841
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of hepatitis B in patients with diabetes mellitus in the UK: A population‐based cohort study using the UK Clinical Practice Research Datalink

Abstract: SummaryWe assessed the incidence and prevalence of hepatitis B (Hep B) in patients with or without diabetes mellitus (DM) using the UK Clinical Practice Research Datalink (CPRD). This was a retrospective, observational study of diabetic and nondiabetic cohorts aged 0-80 years using CPRD (NCT02324218). Incidence rates (IR) for each cohort were calcu- The Hep B IR, hospitalization and prevalence were higher in males in both cohorts. In conclusion, the risk of incident Hep B diagnosis in the diabetic cohort was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Our results showed that patients with diabetes had a higher prevalence of HBV and HCV infections than those without. Similarly, a previous cohort study conducted in the United Kingdom observed a higher prevalence of HBV in patients with diabetes than in those without diabetes [ 27 ]. Another previous study from Pakistan Hospital also indicated that patients with diabetes were more associated with HCV infection than the non-diabetic group (OR = 3.03; 95% CI, 2.64–3.48, p < 0.01) [ 28 ].…”
Section: Discussionmentioning
confidence: 59%
“…Our results showed that patients with diabetes had a higher prevalence of HBV and HCV infections than those without. Similarly, a previous cohort study conducted in the United Kingdom observed a higher prevalence of HBV in patients with diabetes than in those without diabetes [ 27 ]. Another previous study from Pakistan Hospital also indicated that patients with diabetes were more associated with HCV infection than the non-diabetic group (OR = 3.03; 95% CI, 2.64–3.48, p < 0.01) [ 28 ].…”
Section: Discussionmentioning
confidence: 59%
“…Most studies have not observed a difference in seroprevalence of HBV between diabetic and non-diabetic subjects [7, 10, 20, 21]. Only a few studies indicate a higher risk of HBV infection in diabetics compared to non-diabetics [6, 22, 23], and a high risk of diabetes mellitus in HBV infected patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no risk factors for HBV infection has been associated with HBV infection in diabetics. However, a recent study conducted in the United Kingdom [23] reported a high prevalence of HBV in diabetics compared to non-diabetics and even a higher hospitalization rate in HBV-infected diabetics compared to non-infected patients. This indicates that more studies are needed in our area and systematic screening of HBV infection in diabetics is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Although comparable HBV datasets are more available in other countries, such as China and the USA, 29–31 there are scarce comprehensive data of HBV in the UK except for data reported from certain populations 32–34 or the primary care population. 5 , 6 We believe this secondary care cohort can start to fill evidence gaps, especially by collating laboratory, imaging and treatment data which are not currently well captured in primary care.…”
Section: What Are the Main Strengths And Weaknesses?mentioning
confidence: 99%